The Effectiveness of Nutrition Education about Stunting Using Video Media on The Knowledge and Attitudes of Mothers of Toddlers - Naomi Burah; Sepsina Reski; Diah Retno Wahyunigrum; Joko Cahyono (Media Publikasi Cendekia Indonesia, 2024)
Stunting is still a global health emergency, threatening children's health and productivity in the future. Stunting in children begins in the family environment. Mothers contribute fully to optimal child growth and development. This study aims to determine the effectiveness of nutrition education about stunting using video media on the knowledge and attitudes of mothers under five. A quasi-experimental study with a pre-post test approach with a control group design was conducted in February – April 2023 at the Teluk Lingga Sangatta Health Center, East Kutai, East Kalimantan. A total of 36 samples were involved in this study by purposive sampling by taking into account inclusion and exclusion criteria. Data were analysed using paired t-tests and independent t-tests. There were differences in knowledge before and after being given nutrition education videos with a value of p-0.000 and differences in attitudes before and after being given nutrition education videos with a value of p-0.000. There are differences in knowledge before and after nutrition education with leaflet p-0.000. There are differences in the attitude of mothers of toddlers before and after nutrition education with leaflet p-0.000. Nutrition education videos are more effective in increasing knowledge compared to the p-0.000 leaflet. Nutrition education videos are more effective in improving attitudes compared to leaflet p-0.001. Nutrition education videos about stunting are more effective in increasing knowledge and attitudes about stunting.